Science Teachers' Perceptions of the School Environment: Gender Differences - Huang, S.l; Fraser, Barry (John Wiley & Sons, Inc., 2009)
Because the school environment has been shown to play an important role in teacher and student performance, we undertook research into the assessment of school environment, differences between female and male science teachers' perceptions of their school environments, and associations between these school environment perceptions and teachers' background characteristics. Although gender differences in science education have attracted both public concern and academic interest, little research has specifically addressed this issue in terms of the school environment. Data were collected from a large sample of 300 female and 518 male science teachers from secondary schools in Taiwan. Statistically significant gender differences were found in most aspects of the school environment, with female science teachers perceiving greater collegiality among teachers, higher gender equity among students, and stronger professional interest, and with male science teachers perceiving lower work pressure and better teacher–student relations. Gender differences in science teachers' perceptions of collegiality, work pressure, and gender equity in the school environment persisted even after controlling for teachers' background and school characteristics. Among the implications are recommendations about administrative policy for improving the school environment for both male and female teachers and about future research on factors associated with teachers' perceptions.